Case Report: Lymphangiogram and embolization for malignant chylothorax in cancer patients - Moon, John T.; Li, Hanzhou; Abdalla, Omar; Swilley, Nicholas (Frontiers in Oncology, 2025)
Tumor-related lymphatic obstruction can cause malignant chylothorax, which can be debilitating. Conventional management includes dietary modifications, percutaneous drainage, and medical management (octreotide), most of which prove refractory in high-output chylothorax cases. Lymphangiogram and embolization in such cases offers a minimally-invasive alternative; however, its use in non-iatrogenic malignant chylothorax is underreported. We present three cases of malignant chylothorax managed with lymphangiogram followed by therapeutic embolization. Case 1: A 70-year-old female with relapsed angioimmunoblastic T-cell lymphoma presents with bilateral chylous effusions refractory to conventional management. Following thoracic duct embolization (TDE) drainage output decreased from over 600 mL/day to less than 200 mL/day, permitting resumption of systemic therapy and subsequent autologous stem cell transplantation. Case 2: A 28-year-old female with ALK-positive non–small cell lung cancer presents with severe respiratory compromise due to extensive mediastinal disease and high-output chylothorax (>1 L/day) refractory to conventional therapy. TDE reduced drainage to less than 150 mL/day, allowing for continued targeted therapy. Case 3: A 70-year-old female with HER2-positive, ER-/PR– breast cancer presents with recurrent right-sided chylothorax despite prior surgical lymphatic ligations. Direct lymphatic leak embolization resulted in marked reduction of chylous output and significant symptom relief. Lymphangiogram with embolization is a safe and effective intervention for malignant chylothorax, regardless of surgical history. Early intervention can alleviate chyle leaks, facilitate ongoing cancer therapy, and improve patient outcomes, making it an important option in multidisciplinary oncology care.